Jewelry of Sapalli Culture - Odiljon A. Khamidov; Gulmira Ch. Kattayeva; Dilnoza U. Yangiboeva (Археология евразийских степей)
During the Bronze Age (2250–1300 BCE), the territory of the Surxondaryo region was inhabited by bearers of a material culture known as the Sapalli culture. To date, around 70 archaeological sites and pottery locations associated with this culture have been discovered, 17 of which have been excavated by various expeditions. Among the artifacts uncovered at Sapalli culture sites are various ornaments resembling those worn by people even today. These include: head and hair ornaments (pins, hairpins, diadems, earrings), neck jewelry (beads, necklaces, pendants, amulets), yfyd jewelery (bracelets, rings). These items vary in craftsmanship techniques and materials used. Particularly notable are zoomorphic and anthropomorphic pins, rosette-shaped pins, amulets featuring animal motifs and swastika symbols, as well as earrings with eye-shaped patterns. This article presents a scientific analysis of 770 pieces of jewelry recovered from major Sapalli culture sites, including: 47 necklaces, 268 beads, 58 pendants, 1 chain, 96 bracelets, 143 pins, 47 amulets, 3 rings, 6 diadems, 101 earrings. This study examines their typology, functions, and historical-archaeological context.